2017
DOI: 10.11648/j.ijsts.20170503.11
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Productivity of Degraded Pasture Land Through Legume Forages over Sowing

Abstract: Abstract:The experiment was undertaken for one season in Northern Ethiopia, at Emba Alaje District, Ayba Peasant Association to evaluate forage yield of the natural pasture over sown with three adapted legume forages. The design was Randomized Complete Block Design replicated three times. The treatments were control, Vicia dayscarpa, Vicia sativa and alfalfa (Hairy peruvian). The size of experimental plots were 100 m 2 (10 m x 10 m) each. Partial Budget Analysis, Dominance Analysis and Marginal Rate of Return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The higher yield was recorded on pasture land over sown with Vicia sativa (3.43 ton/ha) and 17.06% higher than that of the adjacent farmer's practice. The result was similar with Tesfay et al (2017), in Southern Tigray, who observed increased dry matter production of a natural pasture over sown with Vicia sativa (3.96 ton/ha). Other authors have reported increase in pasture production when suitable pasture legumes were successfully incorporated (Walker, 1969;Stobbs, 1969;Lwoga, 1983).…”
Section: Dry Matter Yieldsupporting
confidence: 89%
See 4 more Smart Citations
“…The higher yield was recorded on pasture land over sown with Vicia sativa (3.43 ton/ha) and 17.06% higher than that of the adjacent farmer's practice. The result was similar with Tesfay et al (2017), in Southern Tigray, who observed increased dry matter production of a natural pasture over sown with Vicia sativa (3.96 ton/ha). Other authors have reported increase in pasture production when suitable pasture legumes were successfully incorporated (Walker, 1969;Stobbs, 1969;Lwoga, 1983).…”
Section: Dry Matter Yieldsupporting
confidence: 89%
“…Over sowing of Vicia sativa pasture had higher biomass yield and it is economical to use it for improving degraded pasture lands (Tesfay et al, 2017). Studies show that the average dry matter yield for pasture land over sown with Vicia sativa (3.96 t/ha) and Vicia dayscarpa (3.12 t/ha) in the South Tigray (Tesfay et al, 2017). However, there was no demonstration of legume over sowing on degraded pasture land before this study in the study area.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations